A Study on Cosmetic Products Marketed in Iraq: Microbiological Aspect - A. Razooki, Raghad; N. Saeed, Ebtihal; Hamza, Heyam (Iraqi Journal of Pharmaceutical Sciences, 2017)
Cosmetic products contain variable amounts of nutrients that support microbial growth. Most contaminants in cosmetic products include bacteria such as Staphylococcus, Pseudomonas, Klebsiella, Achromobacter and Alcaligenes. Contaminated water is a likely source of organisms found in cosmetic products. Products such as shampoo, hand and body lotion, facial cleanser, and liquid soaps were analyzed. In this study, out of 60 cosmetic products analyzed, 26.4% were found to be contaminated. Most of the contamination was from bacteria and no fungal contamination was detected. The highest level of contamination occurred in shampoo.Viable bacterial were not recovered from 100%, 92.8%, 91.6% and 89.2% of showed bath soaps, facial cleanser, hand and body lotion and shampoos, respectively. Coliforms were recovered from one sample of shampoos. One isolate of shigella and pseudomonas aeruginosa was detected from two samples of shampoo.Keywords: Microbial contamination, cosmetic